Accounting for Intergenerational Social Mobility in Low- and Middle-Income Countries - Evidence from the Poorest in Ethiopia, India, Peru, and Vietnam - Fabian Könings; Jakob Schwab (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This study investigates intergenerational social mobility and its particular transmission mechanisms in low- and middle-income countries. Using data from Ethiopia, India, Peru, and Vietnam, we estimate the degree to which socioeconomic status persists across generations. We then analyze through which channels this persistence is mediated. Thereby we also consider channels that are of particular relevance in developing countries, such as the need to work in child labor or the time to school. The results illustrate that having a poor instead of a middle-class family background decreases the chances for a child to obtain the highest schooling degree by 20 per cent in the countries under study. Besides transmission factors also identified as determining social mobility in developed countries such as cognitive ability, we find that the time poorer children spend in child labor and the number of additional children living in the household account for large parts of the immobility observed.
Keywords: I24; J62; O15; 330; Intergenerational Social Mobility; Transmission Channels; Low- and Middle-Income Countries; Child Labor